Feasibility of gray-blood late gadolinium enhancement evaluation in young patients with congenital and acquired heart disease - Gonzalez de Alba, Cesar; Moghari, Mehdi H.; Browne, Lorna P.; Friesen, Richard M.; Fonseca, Brian; Malone, LaDonna J. (Frontiers in Cardiovascular Medicine, 2023)
Background Late gadolinium enhancement (LGE) sequences have become common in pediatric cardiovascular magnetic resonance (CMR) to assess for myocardial fibrosis. Bright-blood late gadolinium enhancement (BB-LGE) by conventional phase-sensitive inversion recovery (PSIR) is commonly utilized, but similar inversion time (TI) value of fibrosis and left ventricular (LV) blood pool can make subendocardial areas difficult to assess. A gray-blood LGE (GB-LGE) technique has been described, targeting nulling of the LV blood pool and demonstrating improvement in ischemic scar detection over BB-LGE in adult patients. We sought to evaluate the feasibility of the GB-LGE technique in a young population with congenital and acquired heart disease and compare its ability to detect subendocardial scar to conventional BB-LGE. Methods Seventy-six consecutive patients referred for clinical CMR underwent both BB-LGE and GB-LGE on 1.5 T and 3 T scanners. Conventional PSIR sequences were obtained with TI to null the myocardium (BB-LGE) in short-axis and horizontal long-axis stacks. Same PSIR stacks were immediately repeated with TI to null the blood pool (GB-LGE). Both sequences were reviewed separately a week apart by two readers, blinded to the initial clinical interpretation. Studies were analyzed for overall image quality, confidence in scar detection, confidence in detection of LGE, LGE class, inter- and intra-observer agreement for the presence of scar, and intraclass correlation coefficient (ICC) for total scar burden. Results Overall confidence in myocardial scar detection by BB-LGE or GB-LGE as well as grading of image quality were not statistically different [(p = 1 and p = 1) and (p = 0.53, p = 0.18), respectively]. There was very good inter-observer agreement for the presence of scar on BB-LGE (K = 0.88, 95% CI 0.77–0.99) and GB-LGE (K = 0.84, 95% CI 0.7–0.96), as well as excellent intra-observer agreement for both readers (K = 0.93, 95% CI 0.87–0.99; and K = 0.81, 95% CI 0.69–0.95). Interclass correlation coefficient for total scar burden was excellent for BB-LGE (ICC = 0.98, 95% CI 0.96–0.99) and GB-LGE (ICC = 0.94, 95% CI 0.91–0.97). Conclusions The GB-LGE technique is feasible in the pediatric population with congenital and acquired heart disease. It can detect subendocardial/ischemic scar similar to conventional bright-blood PSIR sequences in the pediatric population.